NATIONAL AND MODERN IN THE MUSIC OF SERBIAN COMPOSERS FROM THE FIRST HALF OF THE 20th CENTURY - TOTAN, Virđinia; COROIU, Petruța-Maria (Studia Universitatis Babes-Bolyai Musica, 2025)
The first half of the 20th century unfolds, in the arts, not only in music, under the pressure of the paradigm shift that leaves its mark on the entire period preceding the First World War. Anyway, once the seeds of modernity sprout, they do not grow satisfactorily, because they will be interrupted by the Second World War. The ideas of national and universal had been developing since the middle of the Romantic century, when the revolutions around 1848 favored the idea of national freedom and unity. It was then that national cultures were born that tended to value the traditional heritage of each cultural and ethnic space. Serbia has taken advantage of these dominances and has achieved, in its turn, a synthesis between the national and the universal - a fact presented by this work.